Islam and Social Media in Indonesia: A Study of the Living Qur'an and Hadith in the Film “Ruqyah: The Exorcism” - Ihsan Nurmansyah; Sherli Kurnia Oktaviana (Al Qalam, 2022)
This paper discusses the phenomenon of the living qur'an and hadith on the ruqyah scene in the film“Ruqyah: The Exorcism” which MD Pictures, Dee Company and Pichouse Films produced in 2017. The film “Ruqyah: The Exorcism” is a religious horror genre film where in each scene there is a phenomenon of the living qur'an and hadith in the form of the use of verses. Al-Qur'an and Hadith of the Prophet in the ruqyah ritual. Therefore, to find out the functional reception of the verses of the Qur'an and the hadith of the Prophet used in the film "Ruqyah: The Exorcism" is to use the theory of functional reception introduced by Ahmad Rafiq. The results of this study are: 1) during the ruqyah process, Ustadz recites the holy verses of the Qur'an in the form of Surah al-Fatihah/1:1-7 and Surah al-Baqarah/2:255 and the hadith of the Prophet no.. 3514 in the Book of Sunan Ibn Majah, the Book of Medicine, the chapter which the Prophet saw as a means of protection. 2) Functional reception on the informative aspect contains the majesty of Allah and the potential of humans who can face the jinn. While the functional reception is in the performative aspect; namely, the jinn in the human body cannot hide and commit deceit, and the jinn can be removed from the human body.